(Z)-4, 4′-Stilbene dicarboxylic acid, the overlooked metal–organic framework linker. Issue 16 (3rd April 2023) - Hunter, Lucy R.; Karlsson, Joshua K. G.; Sellars, Jonathan D.; Probert, Michael R.
Abstract : The synthesis of 10 lanthanide metal–organic frameworks that incorporate the isomeric ( Z )-4, 4′-stilbenedicarboxylic acid. These form 2D and 3D frameworks, uncovering a previously unknown underlying net topology, lmj1, as well as time dependant dimensionality. Abstract : Metal–organic frameworks exhibit a broad and diverse structural portfolio, with rational structural engineering of frameworks becoming increasingly desirable. Fine-tuning the metal–ligand combination offers a simple way to adjust a framework's physical and chemical properties. One route to synthesising frameworks with new physical properties and topologies without altering the chemical composition is through the use of ligand isomers. Whilst trans -stilbene derivatives, such as ( E )-4, 4′-stilbene dicarboxylic acid have been exhaustively studied producing numerous unique frameworks, its ligand-originated isomer, cis -stilbene derivative ( Z )-4, 4′-stilbene dicarboxylic acid has not. Herein, we describe the synthesis of ten lanthanide ( Z )-4, 4′-stilbene dicarboxylic acid frameworks, five possessing non-interpenetrating 2D sheet structures and five microporous 3D frameworks with 1-dimensional pore channels that incorporate internal voids of up to 5.2 Å in diameter. These three-dimensional frameworks have a hitherto unrecognised underlying net topology, now registered as lmj1 .